Serum proteomics identify biomarkers and pathogenesis of portopulmonary hypertension diagnosed based on echocardiography - Jialin Du; Yifu Zhang; Diandian Hao; Hui Wang; Yulin Ren; Yuze Song; Xiaoyu Wen (Scientific Reports)
Abstract Portal pulmonary hypertension (PoPH), a severe complication of portal hypertension (PHTN), is marked by elevated pulmonary arterial pressure, but its pathophysiological mechanisms are unclear. This study used proteomics to identify differentially expressed proteins (DEPs) and genes in Patients with PoPH compared to those with PHTN and healthy controls (HC), aiming to uncover potential biomarkers for diagnosis and treatment. Patients with liver cirrhosis and PHTN, admitted between January 2023 and May 2024, were classified into PoPH and non-PoPH (PHTN) groups based on echocardiography. Serum from 12 PoPH, 12 PHTN, and 6 HC was analyzed using data-independent acquisition (DIA) proteomics to identify DEPs. Protein-protein interaction (PPI) networks identified key DEPs, and ELISA was performed for biomarker validation. Compared to HC, 374 proteins were upregulated and 115 downregulated in PoPH, while 18 were upregulated and 38 downregulated in PHTN. KEGG and GO analyses linked DEPs to immune response, metabolism, and cell signaling. Thirty-five proteins distinguish PoPH from HC and PHTN. Vitronectin (VTN, P04004) was correlated with RDW (R = -0.56, P < 0.01) and PLT (R = 0.52, P < 0.01). ELISA confirmed lower VTN levels in PoPH (P < 0.05). This study identified 35 serum proteins involved in PoPH, with VTN as a potential biomarker for distinguishing PoPH from PHTN and HC. Further research is needed to explore these findings.